PENGARUH KONSTANTA LAJU TRANSPORT ORGAN PANKREAS PADA PENCAPAIAN KONSENTRASI GLUKOSA DARAH NORMAL DENGAN PEMODELAN - Asra, Asmi (2302-0792, 2013)
Through the study replica regulatory process glucose and insulinconcentrations in the body, it has studied the influence of parametermechanisms of pancreatic organ transport rate constant (K) onachieving normal levels of glucose concentration. In this study hasbeen carried out curve fitting method between clinical data andmodel equations glucose and insulin concentrations for the threeconditions of the patient, namely: glucose low, normal and high ofsix patients. From the results obtained in modeling the effect turnspancreas transport rate constant prices is significant enough glucosedetermination in the model equations for the achievement of pricestatic final glucose concentrations were normal.